Análise biomecânica do osso maxilar durante a expansão rápida da maxila: efeitos ortodônticos e ortopédicos gerados pelo uso de disjuntores palatinos - Larissa Carvalho Trojan (2014)
The Rapid Maxillary Expansion (RME) technique is used to increase the maxillary transverse dimension by using lateral forces on the posterior upper teeth and it is applied regardless of the stage of occlusal development. The purpose of this clinical procedure is to achieve a normal parabolic shape of the upper dental arch and to place the posterior part of the upper arch outside the lower teeth when in contact. This result occurs essentially due to median palatal suture (MPS) separation. But, other cranial sutures and teeth positions are also affected. This work evaluated the mechanical environment in the maxillary and anterior facial bones, when using conventional and supporting bone expanders. The computational simulations were performed on finite element models based on cone beam computed tomography images of a 12 years old patient. For some analyzes, the median palatal suture (MPS) was considered with different elastic moduli (1 MPa and 0.01 MPa), others with bilinear behavior or the MPS was removed. The results showed a significant increase in stresses and strains in the maxillary bone when used bone supported expander appliances, especially near the mini-implant regions. However, the skeletal effect of RME was approximately three times greater for this appliance type. With the results obtained in this study could be concluded that the presence and stiffness of the sutures influence, quantitatively, the displacement of the bone ends of the MPS and the stresses provided computationally. The bone supported device has a better response in skeletal RME, enabling better clinical outcome with fewer activations. However, as the stress magnitude was considerably larger set, we suggest a protocol with more spaced activation or reduced activation.